Resilensi pasar modal: studi respons investor terhadap fatwa mui no. 83 tahun 2023 melalui analisis event study pada saham perusahaan terkena isu boikot - Fitriaty; Salsa, Salsandra Jihan; Haris, Muhammad Haris Saputra (Jurnal Ilmu Manajemen, 2024)
This study aims to analysis changes in abnormal returns and trading volume activity (TVA) before and after the announcement of MUI Fatwa Number 83 of 2023 on companies that have issue related to Israel to explore the impact of the conflict between Israel and Palestina on the global economy, with a special focus on the response of the global community which can be reflected in boycotts of products affiliated with Israel. Through event study method and Paired Sample T-test test, this study concludes that there is no significant difference in abnormal return and TVA between the period before and after the announcement of MUI Fatwa Number 83 Year 2023. Although the conflict and the fatwa create a level of uncertainty, the findings reflect that investors still maintain high interest in investing in the capital market, providing insight into the dynamics of the capital market and investor attitudes amidst tense geopolitical conditions and potential economic sanctions. The implications of this research can serve as a foundation for designing more adaptive investment strategies in the era of global geopolitical.